2018
DOI: 10.1002/jcph.1276
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Therapy in Acute and Chronic Pain

Abstract: This is an article in the Core Entrustables in Clinical Pharmacology series that describes opioid therapy in acute and chronic pain. Opioid use during surgical procedures or anesthesia is not discussed. Basic pharmacokinetic and pharmacodynamic properties of opioids are reviewed. The safe and effective use of opioids, including clinical assessment and treatment plan, equianalgesic dosing, opioid rotation, opioid risks and side effects, and clinical adherence monitoring are discussed. Individualized opioid use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 45 publications
0
72
0
6
Order By: Relevance
“…In this respect, Opioid maintenance treatments (OMTs) are the gold standard medication for opioid dependence. While opioid medications are CONTACT Benjamin Rolland benjrolland@gmail.com Service Universitaire d'Addictologie de Lyon (SUAL), CH Le Vinatier, Pôle MOPHA, 95 Bd Pinel, Bron 69500, France commonly indicated for treating pain [8], when used as OMTs, they have their specific indication and their specific rules of use. Maintenance antagonist treatments, such as long-acting naltrexone, have also proven some efficacy [9], but are regarded as second-choice treatment, that is, if OMTs have been ineffective or were not available.…”
Section: Current Best Treatments For Opioid Dependencementioning
confidence: 99%
“…In this respect, Opioid maintenance treatments (OMTs) are the gold standard medication for opioid dependence. While opioid medications are CONTACT Benjamin Rolland benjrolland@gmail.com Service Universitaire d'Addictologie de Lyon (SUAL), CH Le Vinatier, Pôle MOPHA, 95 Bd Pinel, Bron 69500, France commonly indicated for treating pain [8], when used as OMTs, they have their specific indication and their specific rules of use. Maintenance antagonist treatments, such as long-acting naltrexone, have also proven some efficacy [9], but are regarded as second-choice treatment, that is, if OMTs have been ineffective or were not available.…”
Section: Current Best Treatments For Opioid Dependencementioning
confidence: 99%
“…Morphine milligram equivalent (MME) is a value assigned to opioids to represent their relative potencies. [26] It is determined by using an equivalency factor to calculate a dose of morphine that is equivalent to the ordered opioid. Some recommendations are to limit new opioid users to <50 MME/day.…”
Section: Opioid Equivalent Dosingmentioning
confidence: 99%
“…Some recommendations are to limit new opioid users to <50 MME/day. [26] Morphine equivalent dosing (MED) determines a patient's cumulative intake of any drugs in the opioid class over 24 hours in an effort to help reduce to likelihood of overdose. Tracking daily MED totals can help to: minimize the potential for prescription drug abuse/misuse, reduce the number of unintentional overdose deaths associated with pain medications.…”
Section: Opioid Equivalent Dosingmentioning
confidence: 99%
“…[8][9][10][11] This work focuses on the non-analgesic use of opioids as a bio-renewable resource capable of packaging DNA. While opioids are predominantly used for their potent analgesic properties, serving as one of the major drug classes within the pharmaceutical industry, [12,13] specific architectures were recently identified to have DNA binding properties. [14] In that study, we identified morphine (MC3), oripavine (OC3) and heterocodeine (HC3) C 3 -opioids could condense DNA.…”
Section: Efficient Dna Condensation By a C 3 -Symmetric Codeine Scaffoldmentioning
confidence: 99%